2009 IEEE International Electron Devices Meeting (IEDM) 2009
DOI: 10.1109/iedm.2009.5424370
|View full text |Cite
|
Sign up to set email alerts
|

RTS-like fluctuation in Gate Induced Drain Leakage current of Saddle-Fin type DRAM cell transistor

Abstract: RTS (random telegraph signal)-like fluctuation in GateInduced Drain Leakage (GIDL) current of Saddle-Fin (S-Fin) type DRAM cell transistor was investigated for the first time. Furthermore, two types of fluctuation which have apparently different τ high (average time duration of high leakage state) to τ low (average time duration of low leakage state) ratio were investigated, and it was found that the energy difference between bistable levels is similar to that of the junction leakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…These properties are the same as those of channel RTS of MOSFETs 25) and GIDL-RTS found in non-stressed device. 10) The GIDL-RTS was measured as a function of drain to gate bias voltage (V DG ) as shown in Fig. 9.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These properties are the same as those of channel RTS of MOSFETs 25) and GIDL-RTS found in non-stressed device. 10) The GIDL-RTS was measured as a function of drain to gate bias voltage (V DG ) as shown in Fig. 9.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, RTS-like fluctuation in gate induced drain leakage (GIDL-RTS) current of recess channel type DRAM cell transistor was observed and it was reported that GIDL-RTS is deeply related to VRT in DRAM. 10) It is generally known that the RTS in channel current of metal-oxide-semiconductor field-effect transistors (MOSFETs) originates from the oxide-trap-induced carrier number and surface mobility fluctuations. [11][12][13][14][15][16][17] And, the origin of VRT in DRAM and GIDL-RTS has been attributed to metastable defects in Si bulk.…”
Section: Introductionmentioning
confidence: 99%
“…The GOBD phenomenon has three stages: development of Trap Assisted Tunneling (TAT) current, soft breakdown (SBD), and hard breakdown (HBD). In [5], the TAT gate leakage current is explained by the T-D model and the trap configuration. The leakage current steadily increases as a function of stress time with increasing numbers of traps.…”
Section: Introductionmentioning
confidence: 99%
“…Reverse current at the drain junction is one of the most prominent leakage components in MOS transistors. [1][2][3] Thermal generation via electronic states (traps) is the main mechanism for the current in the reverse-based pn junction. [4][5][6] In the drain junction of MOS transistors, most of the states are located at or near the interface between the drain and gate oxide.…”
Section: Introductionmentioning
confidence: 99%